2005
DOI: 10.1017/s0022029905001202
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of genes encoding proteolytic enzymes during mammary gland development

Abstract: The mammary gland undergoes extensive tissue remodelling during each lactation cycle. During pregnancy, the epithelial compartment of the gland is vastly expanded (Benaud et al. 1998). At the end of lactation the epithelial cells undergo apoptosis and adipocyte differentiation is induced (Lilla et al. 2002). Ductal and alveolar growth during puberty and pregnancy, and the involution process require the action of proteolytic enzymes (including matrix metalloproteinases, plasminogen and membrane-peptidases) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…6b) with peaks of expression during pregnancy and involution. A large number of other MMPs and other proteolytic enzymes mimic this expression pattern [Sorrell et al, 2005;Flint et al, 2006]. If the expression of MMP3 and EMMPRIN are put in relationship to one another, the expression pattern largely follows that of MMP3 (Fig.…”
Section: Analysis Of Emmprin Expression During Mouse Mammary Gland Dementioning
confidence: 91%
See 1 more Smart Citation
“…6b) with peaks of expression during pregnancy and involution. A large number of other MMPs and other proteolytic enzymes mimic this expression pattern [Sorrell et al, 2005;Flint et al, 2006]. If the expression of MMP3 and EMMPRIN are put in relationship to one another, the expression pattern largely follows that of MMP3 (Fig.…”
Section: Analysis Of Emmprin Expression During Mouse Mammary Gland Dementioning
confidence: 91%
“…The positions of ets and AP1 transcription factor binding sites are indicated in Figure 2a. These sites have been shown to mediate most of the regulatory events at MMP promoter elements [Sorrell et al, 2005]. In MacT cells all four constructs show an EMMPRIN mediated down-regulation; even the construct pT-MMP3-luc3, which contains only a 59 bp minimal MMP3 promoter.…”
Section: Analysis Of Mmp Expression In Response To Emmprin Co-transfementioning
confidence: 98%
“…The extracellular proteases are generally more abundant during mammary involution as this involves copious restructuring of the mammary gland, whereas their expression is inhibited during lactation (Sorrell et al 2005). Microarray expression profiling has shown that MMP3, MMP14, and ADAM9 are markedly up-regulated during pregnancy and involution, and MMP3, MMP7, and MMP12 are induced at involution, with MMP3 showing the most profound elevation.…”
Section: The Mammary Remodeling Programmentioning
confidence: 99%
“…Different localized levels of MMP gene expression have also been demonstrated in breast cancer cell xenografts that were recruited by stromal cells (Haupt et al, 2006). In addition, deficiency of individual MMP genes such as MMP-3 or plasminogen in a number of knock-out mice causes alterations to mammary gland structure and impairment of lactation (Sorrell et al, 2005). There is also evidence for highly invasive MDA-MB-231 breast carcinoma cells, which display over-expression of MMP-1, MMP-3, and MMP-13 to be correlated with invasive properties (Balduyck et al, 2000).…”
Section: Introductionmentioning
confidence: 97%